Inequalities in COVID-19 vaccination coverage in Peru: An ecological study - Al-kassab-Córdova, Ali (2023)
Objective: To assess the correlation between COVID-19 vaccination coverage and the Human Development Index (HDI) at the provincial level in Peru. Study design: Ecological study. Methods: We conducted a cross-sectional ecological study based on secondary data analysis. Coverages of the first, second, and third doses of the vaccine against COVID-19 and the HDI were evaluated. The magnitude of the correlations was assessed using Spearman's rank correlation coefficients with their corresponding bootstrapped 95% confidence intervals (95% CI). Scatter plots were also constructed. Results: A total of 196 provinces were included. There was a moderate correlation between the first dose of the COVID-19 vaccine and the HDI (r = 0.3807 [95% CI 0.2585–0.5030], p < 0.0001). The same direction was found for the second (r = 0.4064 [95% CI 0.2853–0.5276], p < 0.0001) and third dose (r = 0.4435 [95% CI 0.3201–0.5669], p < 0.0001). Conclusions: A positive correlation was found between COVID-19 vaccination coverage and the HDI, suggesting the presence of inequalities in access to vaccines. Individualised strategies are needed in lower HDI regions to tackle inequalities.